Fresh frozen cadavers in surgical teaching: a gelatine arterial infusion technique - Jansen, Shirley; Kirk, D.; Tuppin, K.; Cowie, M.; Bharadwaj, A.; Hamdorf, J. (John Wiley & Sons, 2011)
Background: Fresh frozen human cadavers have been used at the Clinical Trainingand Evaluation Centre, The University of Western Australia, Perth, WA for years andare an excellent model for surgical dissection thanks to their representative tissuequality. Differentiation between artery and vein can be difficult as both collapse postmortem. A historical technique was therefore refined to increase arterial rigidity usinggelatine prior to freezing.Methods: Two fresh human cadavers were selected after ethical approval. Gelatinewas infused into the carotid artery in one, and into the common femoral artery in thesecond at a more dilute concentration. In both cases, infusion continued until the rateslowed spontaneously indicating filling prior to setting. The cadavers were frozenaccording to our standard policy and thawed for a teaching course.Results: These were observational. Examination by palpation and dissection afterfreezing and subsequent thawing revealed arterial turgor to have developed at thepopliteal and brachial levels in the first cadaver, and to the distal vessels in the second.Arterial/venous discrimination was therefore enhanced and confirmed by participantfeedback on subsequent courses.Conclusion: The fresh frozen cadaver is already a superior model for teaching thanksto its near life-like representation of tissue quality and handling. A successful techniquefor infusion of gelatine into the arterial tree of fresh human cadavers prior tofreezing has been refined resulting in enhancement of arterial/venous discriminationduring anatomical, interventional and surgical teaching, further optimizing its use inteaching and this now our standard means of preparation.